The knight of the woeful countenance going to extirpate the National Assembly. - (:unkn) unknown (Holland, William, 1790)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; J. Dodsley (Bookseller); Burke, Edmund, 1729-1797 -- Reflections on the revolution in France.; Dodsley, James, 1724-1797